2018
DOI: 10.1063/1.5012994
|View full text |Cite
|
Sign up to set email alerts
|

The origins and properties of intrinsic nonradiative recombination centers in wide bandgap GaN and AlGaN

Abstract: Large electron capture-cross-section of the major nonradiative recombination centers in Mg-doped GaN epilayers grown on a GaN substrateThe nonradiative lifetime (s NR ) of the near-band-edge emission in various quality GaN samples is compared with the results of positron annihilation measurement, in order to identify the origin and to determine the capture-cross-section of the major intrinsic nonradiative recombination centers (NRCs). The room-temperature s NR of various n-type GaN samples increased with decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 74 publications
6
103
0
4
Order By: Relevance
“…Furthermore, it should be noted that HTA could also lead to absorption by formation of group‐III and N vacancies, which are suspected of being able to cluster and form nonradiative recombination centers. [ 26 ] The aim of further process optimization must in any case be to avoid UV absorption and hence to avoid the formation of intrinsic defects during AlGaN annealing.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it should be noted that HTA could also lead to absorption by formation of group‐III and N vacancies, which are suspected of being able to cluster and form nonradiative recombination centers. [ 26 ] The aim of further process optimization must in any case be to avoid UV absorption and hence to avoid the formation of intrinsic defects during AlGaN annealing.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, A. Armstrong et al have identified surface deep-level defects and an effective passivation mechanism of an AlGaN shell on GaN NWs [29]. Fundamentally, the AlGaN shell is likely to reduce the point defects on the surface of GaN core NWs due to lower surface mobility of Al, as well as a lower formation energy of vacancies in the AlGaN layer than that in GaN core NWs [30][31][32][33]. For this reason, it is necessary to conduct a detailed investigation to gain insight into the trapping effect of point defects by the AlGaN undershell in terms of its structural and optical impacts on coaxial GaInN/GaN MQS NWs.…”
Section: Introductionmentioning
confidence: 99%
“…The backdiffusion of positrons in the doped samples induces much more gradual reduction of the S parameter. Typically, a higher S parameter indicates more positrons getting trapped at vacancy defects such as the Ga vacancy V Ga in GaN [32][33][34], or positrons getting trapped at bigger vacancy defects. However, the increase in the S parameter is in this case associated with the increase of the effective positron diffusion length.…”
Section: Resultsmentioning
confidence: 99%